Swot Analysis of Corn Plant in Nganjuk District - Endro Puji Astoko; Nunuk Helilusiatiningsih (East Asian Journal of Multidisciplinary Research, 2023)
Corn is a food commodity as a staple food besides rice in Indonesia. Corn is a plant that can be planted in rice fields or gardens. The aim of the research is to study the SWOT analysis of corn plants spread across Nganjuk Regency. The research method uses quantitative descriptive. The results of the SWOT analysis of corn plants in Nganjuk Regency are as follows: average corn production, total annual production capacity is 203,402 tons. The obstacles that occur in the field are the Human Resources management system for warehouse managers, the operations of warehouse institutions are relatively low. The market network is considered to be less extensive and the sense of trust in corn farmers is still low while purchasing prices from farmers are low, therefore farmers sell their products in local markets. Supply chain management is also still very low. So it is very necessary to improve the management of farmer empowerment, and the quality of all parties involved must be improved in order to produce good results.